The influence of zinc oxide on the anticorrosive behaviour of eco - friendly paints - Deya, Marta Cecilia (2004)
Zinc phosphate and related compounds have achieved wide application as suitable replacements for toxic and pollutant zinc Chromates and lead oxides which were employed as anticorrosive pigments for paints. The behaviour of inorganic phosphates and tripolyphosphates may be improved by a suitable selection of complementary pigments. The objective of this research work was to study the effect of substituting talc by zinc oxide in the pigment formula of anticorrosive alkyd paints. Different inorganic phosphates and tripolyphosphates were selected as active pigments. Paints with a pigment volume concentration/critical pigment volume concentration (PVC/CPVC) equal to 0.8 were formulated and their anticorrosive efficiency tested through accelerated and electrochemical tests. Results showed that the incorporation of zinc oxide to the pigment formula improved corrosion resistance of painted steel, especially in the case of tripolyphosphates.